2014
DOI: 10.3390/su6063374
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and Analysis of Urban Competitiveness of Chinese Provincial Capitals in 2010 under the Constraints of Major Function-Oriented Zoning Utilizing Spatial Analysis

Abstract: Urban competitiveness aids local development by encouraging the exploitation of opportunities for economic development and by enhancing overall performance. Previous studies have evaluated urban competitiveness primarily from an economic perspective and few studies have considered locational conditions as factors that might influence local industrialization and urbanization. In response to the publishing of a national plan for the development of major function-oriented zones (MFOZs) in 2010, the present essay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 31 publications
0
28
0
1
Order By: Relevance
“…Although these studies have various dimensions of urban competitiveness, the common core dimensions include economic competitiveness, social competitiveness and environmental competitiveness [1,2,9,15,16]. This balanced approach suggests an equal importance of these dimensions, marking a significant scholarly advancement from the economic-centric approach to urban competitiveness.…”
Section: Environmental Sustainability and Urban Competitivenessmentioning
confidence: 99%
“…Although these studies have various dimensions of urban competitiveness, the common core dimensions include economic competitiveness, social competitiveness and environmental competitiveness [1,2,9,15,16]. This balanced approach suggests an equal importance of these dimensions, marking a significant scholarly advancement from the economic-centric approach to urban competitiveness.…”
Section: Environmental Sustainability and Urban Competitivenessmentioning
confidence: 99%
“…The main conclusion is that developed countries have a low environmental impact from production stage and developing countries from consumption stage. Moreover, in [24] there was an excellent literature review of papers that includes the environment in urban competitiveness that shows the great importance that this relationship has in the studies developed; however, after reading this paper we do not have a clear conclusion as the majority of studies have been developed for Chinese cities [27][28][29][30]. Therefore, the literature review has showed a gap because, to the best of our knowledge, there are no papers that consider the effect of sustainability on the response to the economic crisis.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, many high-tech industrial parks have been established in Fuzhou and Pingxiang recently, which has made a great contribution to improving the quality of local industrial development. Additionally, Nanchang enjoys the largest industrial economy in Jiangxi Province, which accounts for about a quarter of the industrial GDP in this province [43], and as the capital city of Jiangxi Province, Nanchang enjoys obvious advantages compared with other cities in many aspects (e.g., policy, technology, and talent) [44]. However, the PIGDs for Shangrao and Ganzhou have not made significant progress, nor have its decomposition indicators.…”
Section: The Pigd and Its Decomposition Indicatorsmentioning
confidence: 99%
“…this province [43], and as the capital city of Jiangxi Province, Nanchang enjoys obvious advantages compared with other cities in many aspects (e.g., policy, technology, and talent) [44] …”
Section: Spatio-temporal Pattern Of Pigd and Its Decomposition Indicamentioning
confidence: 99%